2007
DOI: 10.1038/sj.icb.7100055
|View full text |Cite
|
Sign up to set email alerts
|

Models for antigen receptor gene rearrangement: CDR3 length

Abstract: Despite the various processing steps involved in V(D)J recombination, which could potentially introduce many biases in the length distribution of complementarity determining region 3 (CDR3) segments, the observed CDR3 length distributions for complete repertoires are very close to a normal-like distribution. This raises the question of whether this distribution is simply a result of the random steps included in the process of gene rearrangement, or has been optimized during evolution. We have addressed this is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 65 publications
1
50
0
Order By: Relevance
“…Co-clustering the data from the TIV and pH1N1 datasets for each participant revealed that on average 52 clusters were shared between their TIV and pH1N1 plasma cell datasets, equating to 1% of the total number of clusters present in the two datasets. As the probability of the same CDR3 being produced during two independent recombination events during the lifetime of a single individual is practically zero, it is likely that these shared clusters represent memory recall of the same B cell lineage1628. On average, 98% of these recalled clusters were classed as mutated following pH1N1 vaccination, compared to 88% of total clusters (p  =  0.0002; Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Co-clustering the data from the TIV and pH1N1 datasets for each participant revealed that on average 52 clusters were shared between their TIV and pH1N1 plasma cell datasets, equating to 1% of the total number of clusters present in the two datasets. As the probability of the same CDR3 being produced during two independent recombination events during the lifetime of a single individual is practically zero, it is likely that these shared clusters represent memory recall of the same B cell lineage1628. On average, 98% of these recalled clusters were classed as mutated following pH1N1 vaccination, compared to 88% of total clusters (p  =  0.0002; Fig.…”
Section: Resultsmentioning
confidence: 97%
“…To study recalled clusters that are likely to be influenza-specific, those present in the TIV dataset, that then re-appear in the pH1N1 dataset were found for each participant. As the probability of the same CDR3 being produced during two independent recombination events during the lifetime of a single individual is practically zero, it is likely that these shared clusters represent memory recall of the same B cell lineage1628. On average, there were 52 clusters for each participant found in both the TIV and pH1N1 datasets, equating to approximately 1% of the total number of clusters present in the two datasets.…”
Section: Resultsmentioning
confidence: 99%
“…Estimates on the total possible diversity in immunoglobulins vary depending on the assumptions being made, ranging from 10 13 to more than 10 50 (2,3). Despite the large range, it is sufficiently clear that sequence variation is large, and based on these numbers one could statistically assume that antibody sequences found in a person must be unique, and that such antibodies will not be found in other subjects.…”
mentioning
confidence: 99%
“…Antibodies, or immunoglobulins, are highly complex molecules with large variation in their amino acid sequence. The possible diversity in immunoglobulins is estimated between 10 13 and 10 50 and therefore the finding of similar or even identical sequences in different individuals by chance is in theory, highly unlikely [14], [15]. However, studies of different research groups have recently demonstrated that despite this theoretical small chance to have identical antibodies among individuals, it is possible to identify similar or identical sequences [16]–[19].…”
Section: Introductionmentioning
confidence: 99%